CHRISTIANITY, IGBO TRADITIONAL RELIGION AND ISLAMIZATION - Oparanozie, Promise (PEOPLE: International Journal of Social Sciences, 2019)
In all Igbo society, there are no atheists. This is because religion in the indigenous Igbo culture was not an independent institution. It is an integral and inseparable part of the society. Every Igbo man has the idea of the existence of the Supreme Being and worships him with every reverence. There was peace and tranquility among the people. The people had fear and respect for sacred objects. Morality, respect for elders and the fear for the gods were highly regarded. Since the arrival of Christianity and Islam in the Igbo society, the peace and stability in the Igbo society has been threatened. Christians and Muslims have resorted to unhealthy competition for religious and political power in order to assert their rights and supremacy which has resulted to violent encounter and consequently created a pluralized religious environment in the traditional Igbo society. Yet those who converted to Islamic and Christian religions still resort to the tradition religion in the face of serious challenges. This work among other things adopts a functionalist theory to arrive at its findings. And the methodologies such as sociological, phenomenological, anthropological and historical were utilized to harmonize on the issue of Islamization and Christian inversion of the traditional Igbo society. This work recommends that a proper enculturation theology be applied as a solution on the ongoing dialogue between faith and culture. It observed that the Igbo man is highly religious and have had much religious experience before the advent of Christianity and Islam. This work therefore concludes that all the element of foreign culture should be contextualized and adapted into the Igbo tradition.